DEVELOPMENT OF WEB-BASED INFORMATION SYSTEM (DISTANCE EDUCATION INFORMATION SYSTEM) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The paper describes Distance Education Information System. The aim o f the system is to provide effective information exchange between teachers and students and to store information about students progress marks. Based on theoretical knowledge and practical experience tasks for such an information system are described, as well as possible ways of implementation and the real product - Distance Education Information System.